Effects of the First Wave of the COVID-19 Pandemic on the Work Readiness of Undergraduate Nursing Students in China: A Mixed-Methods Study - He L; Dela Cruz JRA (Dove Medical Press, 2024)
Lifang He,1,2 Jean Rizza A Dela Cruz3 1School of Nursing, XiangNan University, Chenzhou, 423000, People's Republic of China; 2College of Nursing and Allied Health Sciences St.Paul University Manila, Manila, 1004, Philippines; 3Department of Nursing Olivarez College Tagaytay, Tagaytay City, 4120, PhilippinesCorrespondence: Jean Rizza A Dela Cruz, Department of Nursing Olivarez College Tagaytay, Tagaytay City, 4120, Philippines, Tel +639175507389, Email jeanrizza@icloud.comBackground: Newly graduated nurses with strong work readiness are more likely to smoothly transition from school to clinical settings. However, even before the pandemic, this transition from nursing graduate to clinical nurse was often challenging. Therefore, this study aims to investigate the impact of the initial wave of COVID-19 on the work readiness of nursing students.Methods: A convergent mixed-method design was employed. For the quantitative study, an online cross-sectional survey was conducted among 500 graduating nursing students from four Chinese public higher education institutions. The questionnaire comprises three parts: socio-demographic information, the Chinese version of the Work Readiness Scale for Graduate Nurse, and a questionnaire on the socio-behavioral impact of COVID-19 on the general population. In the qualitative study, a semi-structured interview was carried out with 8 students who took part in the survey. The results from both parts were integrated using the "Pillar Integration Process".Results: The study identified six key pillars: "Graduating nursing students possess fundamental knowledge, skills, and a preparedness in terms of attitude and psychology"; "Specialist knowledge and skills and soft skills for transition from nursing students to clinical nurses need to be strengthened"; "The most obvious impact of COVID-19 on nursing students are the adoption of preventive measures and the limitations in study and daily life due to household confinement"; "Growth in both personal and professional awareness"; "Negative effects of fear and anxiety"; and "Negative effects of household confinement".Conclusion: Graduating nursing students require additional preparation in specialized nursing knowledge, skills, and soft skills to make a successful transition from students to clinical nurses. It is important to acknowledge that the impact of COVID-19 on students' work readiness has both positive and negative aspects. Therefore, whether during the pandemic or post-graduation, these students will benefit from increased support from universities and hospitals.Keywords: work readiness, COVID-19, nursing students, nursing education, mixed methods, pillar integration process